ANALISIS PERBEDAAN RESPONSIVENESS PELAYANAN RAWAT JALAN PADA PASIEN UMUM DAN PASIEN BPJS DI BALAI KESEHATAN INDERA MASYARAKAT (BKIM) PROVINSI JAWA TENGAH - Hanifah Iskhia Dilla; Septo Pawelas Arso; Eka Yunila Fatmasari (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Responsiveness is an important aspect for all classes and types of patients in improving health status which is one of the goals of the National Health System. BKIM which is a Technical Implementation Unit of Central Java Provincial Health Office which has responsibility in improving the health status of community senses must provide health services that are neat, targeted, targeted and responsive for all classes or types of patients. From the observation by the researcher that there are still unresponsiveness responsiveness aspects such as officer friendliness, patient comfort, and patient's confidentiality that turns out in the responsiveness aspect aspect that is given there is difference of perception felt between general patient and BPJS patient. So it is necessary to do comprehensive research to know the difference of responsiveness of general patient and BPJS patient in BKIM Prov. Central Java. The method used is quantitative method with cross-sectional approach. The sample was 82 general patients and 83 BPJS patients who fulfilled the inclusion criteria. From the results of the study that there is a significant difference between responsiveness of general patients and responsiveness of BPJS patients. The most responsiveness aspects that differ between general patients and BPJS patients are aspects of staff friendliness, waiting time aspect, patient confidentiality aspect, and the aspect of patient's freedom in choosing health services. And the aspect that has less value than the general patient and BPJS patient is the comfort aspect of the patient. BKIM Prov. Jateng is expected to always improve health service to be more responsive service so that always can fulfill society expectation and improve patient satisfaction and pay attention to aspect of hospitality, waiting time, patient comfort, patient confidentiality and patient's freedom in choosing health service.